Computational Thinking with the Guided-Discovery-Learning Model Using Ethnomathematics-Based LKPD.EDM in Elementary School - Solihin, Annas; Habibie, Ramadhan Kurnia; Rahmawati, Ika (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2024)
One aspect supporting the application of the ethnomathematics approach is the use of culture-based student worksheets (LKPD). This research aims to develop and implement student worksheets (LKPD.EDM) based on Engklek in Mathematics (LKPD.EDM) to teach the concept of composition and decomposition of numbers in elementary schools. These LKPDs were designed using the Guided-Discovery-Learning (GDL) model to improve elementary school students' computational thinking skills. The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The study involved 20 fourth-grade students in the learning process. Data collection methods included observation, interviews, questionnaires, and initial and final tests. Data analysis involves analysis of development results, analysis of questionnaire results, and analysis of test results. The research results indicate that the use of LKPD.EDM effectively improves students' understanding of mathematical concepts and computational thinking abilities. Evaluation results show a significant increase in post-test scores, along with positive responses from students towards learning with LKPD.EDM. In conclusion, LKPD.EDM is suitable for teaching the composition and decomposition of numbers, as well as enhancing computational thinking skills among elementary school students.